Studi In Vitro: Efek Anti Kolesterol Ekstrak Daun Rambusa (Passiflora foetida L) - Evi Mulyani (Jurnal Surya Medika (JSM), 2019)
The Rambusa plant (Passiflora foetida L) is known to contain compounds for various treatments, empirically the people in Indonesia, especially Central Kalimantan, use the leaves of rambusa known as the cemot plant to reduce cholesterol levels in the blood. Chemically, cholesterol is a complex compound produced by the body with various functions, including producing sex hormones, adrenal cortex hormones, vitamin D, and the production of bile salts that help the intestines to absorb fat. So, if the dose is right or reasonable, the role of cholesterol in the body will be optimal. The purpose of this study was to determine the effect of anticholesterol in rambusa leaf extract. This study is an experimental study. The anticolesterol effect was tested by the modified enzymatic endpoint cholesterol method. The leaf extract of Rambusa was made with a concentration of 0.5 mg/ml, 1 mg/ml and 1.5 mg/ml as a positive control (multiplier) using simvastatin which was then reacted with reagent R1 and read the results using a photometer and UV-spectrophotometer. Vis with a wavelength of 546 nm. The measurement results using a photometer showed standard cholesterol levels (control negative) 200 mg/dl, positive control 195 mg/dl, 144 mg/dl (extract 0.5 mg/ml), 108 mg/dl (extract 1 mg/ml) and 103 mg/dl (extract 1.5 mg/ml). While the measurement of cholesterol absorbance and concentration using a UV-Vis spectrophotometer at a wavelength of 546 nm 0.179±159.8 mg/dl (Control positive), 0.123±109.8 mg/dl (extract 0.5 mg/ml), 0.110±98.2 mg/dl (extract 1 mg/ml), and 0.109±97.3 mg/dl (extract 1.5 mg/ml). As a conclusion, Rambusa leaf extract can reduce cholesterol levels in vitro.